Investigating the Structural Model of Predicting Sleep Disorders Through Symptoms of Rumination with the Mediating Role of Social Support in Dialysis Patients - Farhad Ghorbani; Amin Rafiepoor; Niloufar Tahmouresi; Reza, Hosseinpour (روانشناسی بالینی و شخصیت)
Introduction: This study aims to investigate the structural model that predicts sleep disorders based on symptoms of rumination, with social support serving as a mediating factor among dialysis patients.Method: The design of the current research employed a correlational structural equation modeling approach. The study sample comprised 250 dialysis patients from hospitals in Tehran during the years 2022-2023, selected using a convenience sampling method. The research instruments included the Pittsburgh Sleep Quality Index, as well as the social support and rumination scales developed by Zammit et al. Structural equation modeling was employed for data analysis.Results: The results indicated that social support serves as a mediating factor in the relationship between rumination and sleep disorders. Additionally, the direct relationship between anxiety, depression, and rumination, as well as social support and sleep disorders, was statistically significant.Discussion and Conclusion: In conclusion, social support and rumination significantly impact the sleep disorders experienced by dialysis patients. Therefore, it is essential to focus on identifying and addressing the effective and causal factors when developing therapeutic interventions for these sleep disorders.